Akibat Hukum atas Alokasi Anggaran Pendidikan yang Kurang dari 20% Anggaran Pendapatan dan Belanja Daerah - Nina Anggreni (Jurnal Mengkaji Indonesia, 2023)
Abstract: The existence of a pandemic has greatly affected the financial capacity of the Regional Government, so that there are regions that have not been able to meet the education budget allocation of at least 20% of the Regional Revenue and Expenditure Budget because the priority for handling and recovering from the impact of the pandemic is dominant and urgent to implement. Purpose: This study aims to provide academic descriptions and recommendations to regional governments in allocating the education budget according to their authority in regional autonomy. Design/Methodology/Approach: Research methods uses normative juridical research methods based on juridical aspects such as: norms, laws and regulations, and legal theories related to the authority to allocate the education budget obtained from scientific works, books, online media, and so on related to the object the research studied. Findings: This study discusses the legitimacy of regional regulations and the legal responsibilities of regional governments that allocate an education budget of less than 20% of the Regional Revenue and Expenditure Budget. Problems arise because there are regions that have not been able to meet the education budget allocation of at least 20% of the Regional Revenue and Expenditure Budget so that the Regional Government and the Regional People's Representative Council are faced with a difficult position when setting/approving the Regional Revenue and Expenditure Budget, because it is considered to have caused delegitimization of the constitution as the highest law. Originality/Value: This research comprehensively explains the legality of regional regulations which in substance have not fulfilled the mandate of the constitution. Then, this study also explains the legal responsibilities that will be faced by regional governments due to the unfulfilled constitutional mandate.